Kajian model kualitas pelayana terhadap keputusan pembelian pada hotel-hotel di Kota Bandung pada masa pandemi covid-19 - Prianka, Winda Gafrilia; Sentika, Sarah; Asqalani Rifai, Muhammad Syakib; Sopiani , Windi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The Covid-19 pandemic has caused many tourism businesses, both restaurants, hotels and tourist objects, to be forced to close. road access closure and also the Implementation of Restricting Community Activities (PPKM). Therefore, researchers conducted research on hotels in the city of Bandung, especially hotels located in the Jalan Riau area of Bandung City by implementing a Service Quality Model Study as an effort to improve room purchasing decisions. Study Technique The data model used in this study is the Path Model Study with SPSS tools. The results of this study indicate that the decision to purchase a room at a 4-star hotel in the city of Bandung, especially in the Jalan Riau area of Bandung City, obtained a score of 56% which is directly influenced by the service quality model.